A study of factors affecting inheritance success in family businesses in Kerala. (11th November 2020) - Bhasi, M.; Renuka, V.V.; Rajkumar, S.
Family business contributes significantly to the Indian economy, their existence and survival is therefore important. Generational transition is the time when many family businesses or business families fail. In this empirical study the effect of selected owner and business related factors on success of inheritance in family businesses in Kerala is examined. Based on the responses from one hundred and fifty current owners of family businesses in Kerala, we have identified the important owner and business related factors that have significant impact on the chance of success of inheritance in the family business. Two owner-related factors, religion and age, and two business related factors, size of business and nature of constitution of organisation were found to have significant impact on the chance of success of inheritance management in family business.